Karakteristik Pasang Surut di Perairan Pantai Samudera Indah Kabupaten Bengkayang Kalimantan Barat - Hutafea, Hutafea; Kushadiwijayanto, Arie Antasari; -, Risko (Program Studi Ilmu Kelautan FMIPA Universitas Tanjungpura, 2023)
Samudera Indah Beach is located in Sungai Raya Kepulauan District, Bengkayang Regency. Tides have a significant influence on the dynamics of the geomorphology of waters, especially coastal waters. The phenomenon of tides in coastal waters can cause regular changes in sea level. Coastal waters are strongly influenced by the highest tides and lowest ebbs. An understanding of tides is necessary because it is one of the important perspectives in monitoring the characteristics of a body of water. This study aims to determine the analysis of tidal harmonics and determine significant fromzahl numbers and types of tides in the coastal waters of Samudra Indah, Bengkayang Regency. Field tide data collection was carried out from March 26 2021 to April 9 2021 which was carried out at Samudra Indah Beach, Bengkayang Regency, West Kalimantan. Research and collection of tidal data was carried out for 15 days. The results showed that the tidal type in the waters of Samudera Indah Beach, Bengkayang Regency, was a mixture of double daily skew with a Formzahl number of 1.3.